A resorcin[4]arene hexameric capsule as a supramolecular catalyst in elimination and isomerization reactions - Lorenzetto, Tommaso; Fabris, Fabrizio; Scarso, Alessandro (Beilstein Journal of Organic Chemistry, 2022)
The hexameric resorcin[4]arene capsule as a self-assembled organocatalyst promotes a series of reactions like the carbonyl–ene cyclization of (S)-citronellal preferentially to isopulegol, the water elimination from 1,1-diphenylethanol, the isomerization of α-pinene and β-pinene preferentially to limonene and minor amounts of camphene. The role of the supramolecular catalyst consists in promoting the protonation of the substrates leading to the formation of cationic intermediates that are stabilized within the cavity with consequent peculiar features in terms of acceleration and product selectivity. In all cases the catalytic activity displayed by the hexameric capsule is remarkable if compared to many other strong Brønsted or Lewis acids.
Keywords: cationic intermediates; encapsulation; organocatalysis; resorcin[4]arene hexamer; supramolecular catalysis